Pelaksanaan Program KKN Membuat Plang Selamat Datang Sebagai Upaya Penambahan Infrastruktur Dukuh Sambiroto - Arlistyo Risyad Pratama Helmi; Ester Ika Ayu Putri Setyanto; Henny Tri Hastuti Hasanah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
KKN is a form of education by providing learning experiences for students to live in society, directly identifying and dealing with community problems as well as efforts to increase the content and weight of education for students and to obtain greater added value for higher education. Infrastructure is a physical system needed to meet basic human needs in the social and economic spheres. In 2023, one of the villages that will be used as a place or location for Real Work Lectures at Sahid University Surakarta is Sindon Village, Ngemplak, Boyolali. Sindon Village is one of the villages in Ngemplak District, Boyolali Regency, Central Java Province. Sindon Village itself consists of 3 hamlets, namely Sambiroto Hamlet, Brajan Hamlet and Manukan Hamlet. Based on surveys and direct observations carried out in Dukuh Sambiroto, it was found that there was no welcome sign. For this reason, the SGM KKN Team carried out a program to make welcome signs to Sambiroto Hamlet. With the aim of providing benefits as a guide. In its implementation, activities ran smoothly and were on target according to the specified time.